Histologic assessment of the intestinal wall following duodenal mucosal resurfacing (DMR): a new procedure for the treatment of insulin-resistant metabolic disease - de Moura, Eduardo G. H.; Ponte-Neto, Alberto M.; Tsakmaki, Anastasia; Aiello, Vera Demarchi; Bewick, Gavin A.; Brunaldi, Vitor O. (Endoscopy International Open, 2019)
Background and study aims Minimally invasive procedures that replicate aspects of bariatric surgery with more favorable safety and tolerability offer an attractive alternative in management of metabolic disease. Duodenal mucosal resurfacing (DMR), an endoscopic procedure using hydrothermal ablation, is designed to remove surface epithelium to allow subsequent epithelial regeneration and a reset to a more insulin-sensitive state.Materials and methods DMR was performed on a healthy pig under general anethesia, approximating the procedure designed for use in humans. Immediately post-DMR, analysis of the histological landscape was conducted in distinct duodenal areas that received ablation treatment.Results DMR submucosal lift and hydrothermal ablation elicited disruption of villous tips and partial disruption of the crypt base with no damage to deeper tissue. Excessive ablation (purposeful double ablation exposure) did incur damage to the underlying muscle layer.Conclusion Our results confirmed that DMR elicits superficial ablation of duodenal villi and crypts. Defining the cellular consequences of ablation and regeneration of the epithelium will aid our understanding of how and why DMR affects metabolic homeostasis.